PENGARUH PENERAPAN E-SPT,E-FILLING DAN E-BILLING TERHADAP TINGKAT KEPUASAN DAN DAMPAK NYA PADA KEPATUHAN WAJIB PAJAK - Afandi Harlim (Prosiding Seminar Nasional Pakar, 2019)
This study aims to analyze the effect of efficacy againstTaxpayer Compliance with service quality as intervening variable in Gunungkidul Region. This research data is obtained from questionnaire (Primary) which is distributed to the Taxpayer using e-filling program in Gunung kidul area. The population of this study is Individual Tax payers whouse e-filling in the area of gunungkidul. The sample used in this study ere 70 respondents. This research uses analytical path. The results of this study indicate that (1) Application of E-Filling System has a significant effect on service quality satisfaction. (2) satisfaction of service quality have a significant effect to taxpayer compliance this is proven through simple linear regression. (3) the application of e-filling affect taxpayer compliance significantly influence taxpayer compliance. (4) e-filling program has an effect on compliance through service quality.